An New Implementation of the Integrated Transport and Health Impacts Model for the United States. (June 2017) - Vargo, Jason; Younkin, Samuel; Patz, Jonathan
Abstract : Background: The Integrated Transport and Health Impacts Modelling (ITHIM) Tool has been used in data-rich environments of the UK, select US metros, and even São Paulo, Brazil. Its use has been limited, in part, because of its data requirements, format, and complexity. This work makes improvements to the US version of ITHIM, in particular to its module for estimating chronic disease burden reduction through change in population-level physical activity, to address these limitations. Methods: Using the R software and language, we have updated and improved the US implementation of ITHIM. The revised model includes improved discretization of the attributable fraction as well as clearer documentation of model runs, changes, and results. Results: These improvements have produced results that were more stable in the face of variability of existing input parameters, particularly population-level non-travel active times. Conclusions: The resulting package for R is freely available software for modeling the health impacts of transportation planning scenarios. We believe these improvements will appeal to a larger user base through its ease of use, improved documentation, and more powerful capabilities.